Cold War rivalry on Brazil’s and Argentina’s nuclear programs: examining military and civilian intentions - Cançado Motta, André Luiz; Silva Ferreira, José Paulo (Conjuntura Austral, 2023)
The objective of this article is to investigate whether Cold War rivalry influenced the development of nuclear programs in Brazil and Argentina. The research employs a qualitative approach and bibliographic analysis of primary sources, including articles, books, and other relevant sources. The main hypothesis is to examine whether the culture of Cold War rivalry stimulated the development of nuclear programs in these countries, analysing the military and civilian intentions behind their nuclear technologies. While it is commonly reported that Latin America was under the influence of the United States (US) and the Soviet Union (USSR) during the Cold War, the cases of Brazil and Argentina show the opposite. Both countries adopted independent nuclear policies, seeking technological transfer through diversified and autonomous partnerships. Additionally, these divergent positions included arguments and actions regarding their respective nuclear policies. However, mutual distrust between Brazil and Argentina regarding the advancement and sophistication of their nuclear programs generated a dynamic similar to the Cold War in the Southern Cone region. This dynamic originated internally based on the logic of the two countries, despite the later creation of joint non-proliferation mechanisms.